(untitled) (CIPEEX, 2025)
The incorrect disposal of solid waste has caused significant environmental impacts, such as increased pollution. In Brazil, much of this waste is discarded in open areas, leading to the proliferation of vectors and health hazards. The National Solid Waste Policy (PNRS), established by Law No. 12.305 of August 2, 2010, mandates waste management in the business environment to ensure proper disposal of solid waste. This work proposes software for preparing a Solid Waste Management Plan (PGRS) for a private educational institution in Anápolis. The study is based on bibliographic research and a methodology for creating the PGRS, which includes stages such as preliminary diagnosis, planning, implementation, and monitoring. A specific solution is proposed for managing indicators and solid waste for the company. The system’s creation and implementation aim to streamline activity control, providing quick and accurate information. This approach meets the educational establishment’s needs, enhancing efficiency, safety, and environmental responsibility.